Finite element optimization of sample geometry for measuring the torsional shear strength of glass/metal joints. Issue 4 (March 2020) - Fakouri Hasanabadi, M.; Malzbender, J.; Groß-Barsnick, S.M.; Abdoli, H.; Kokabi, A.H.; Faghihi-Sani, M.A.
Abstract: Assessment of mechanical properties of glass/metal joints is a challenging process, especially when the application relevant conditions of the joints have to be considered in the test design. In this study, a finite element method (FEM) is implemented to analyze a torsional shear strength test designed for glass-ceramic/steel joints aiming towards solid oxide fuel/electrolysis cells application. Deviations from axial symmetry of the square flanges (ends) of respective hourglass-shaped specimens and also supporting and loading sockets of the test set-up are included in the model to simulate conditions close to reality. Undesirable tensile stress and also shear stress concentration appear at the outer edge of glass-ceramic layers, which are less for the hollow-full specimen. The simulation results show that for a specimen with either 9 mm thick square- or 6 mm thick triangular-flanges, locally enhanced tensile stresses almost disappear, resulting in a symmetric shear stress distribution. The difference between the analytically derived nominal shear strength and the real critical shear stress derived via simulation reduces with decreasing the fracture torque.